2018
DOI: 10.1007/s10140-018-1597-8
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of CT cervical spine after office hours by radiology trainees—analysis of discrepancy rates and RADPEER scores

Abstract: Cervical spine CTs performed after office hours can be safely interpreted by senior radiology trainees to a reasonable degree, although a targeted intervention to improve diagnostic performance of junior radiology trainees may be of clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The sensitivity of junior and senior registrars was 63.2% and 83.3%, respectively, mirroring a trend found in several studies evaluating for correlation between registrar performance and experience 11,12,17,18 . These results highlight the importance of continued supervision and feedback for registrars throughout all years of training, not only during the early years of practice.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The sensitivity of junior and senior registrars was 63.2% and 83.3%, respectively, mirroring a trend found in several studies evaluating for correlation between registrar performance and experience 11,12,17,18 . These results highlight the importance of continued supervision and feedback for registrars throughout all years of training, not only during the early years of practice.…”
Section: Discussionsupporting
confidence: 81%
“…[5][6][7][8][9] A large Canadian study assessing on-call trainees found a major discrepancy rate of 1.0% from 192 CCTs, which was lower than the 2.5% background rate of major discrepancy for all CT regions. 11 A similar study by Yan et al 12 from a Level I trauma centre in Singapore, evaluating 254 after-hours CCTs reported by trainees, described an overall discrepancy rate of 4.7%. These minor differences in discrepancy rates between the current and prior studies may be the result of several factors, including local variations in registrar experience and patient populations.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations